2017
DOI: 10.1111/jpg.12671
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Generation Potential and Depositional Environment of Shales in the Cretaceous Napo Formation, Eastern Oriente Basin, Ecuador

Abstract: Marine shale samples from the Cretaceous (Albian‐Campanian) Napo Formation (n = 26) from six wells in the eastern Oriente Basin of Ecuador were analysed to evaluate their organic geochemical characteristics and petroleum generation potential. Geochemical analyses included measurements of total organic carbon (TOC) content, Rock‐Eval pyrolysis, pyrolysis — gas chromatography (Py—GC), gas chromatography — mass‐spectrometry (GC—MS), biomarker distributions and kerogen analysis by optical microscopy. Hydrocarbon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Baby et al (2013) proposed that Cretaceous Napo Formation source rocks may locally be mature in the eastern slope zone of the basin. Yang et al (2017) proposed that Napo Formation source rocks may be early to peak mature over larger areas of the slope zone based on source rock and maturation analyses.…”
Section: Geological Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Baby et al (2013) proposed that Cretaceous Napo Formation source rocks may locally be mature in the eastern slope zone of the basin. Yang et al (2017) proposed that Napo Formation source rocks may be early to peak mature over larger areas of the slope zone based on source rock and maturation analyses.…”
Section: Geological Backgroundmentioning
confidence: 99%
“…2) (Dashwood and Abbotts, 1990;Baby et al, 2014). Recent studies (Yang et al, 2017;Ma et al, 2020) have demonstrated that there is a close geochemical relationship between Napo Formation calcareous shale source rocks and oil Canfield et al, 1982;Smith, 1989;Dashwood and Abbotts, 1990;White et al,1995;Barragán et al, 2005;. The approximate positions of the oil samples and the sandstone core samples from the Napo Formation M1 Sandstones are shown in the chronostratigraphic profile to the right (red and blue circles).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Along with profound exploration and exploitation (Figure 1), the oilfield at the No.1 area Yaojia formation reservoir in Daqing has come into the ultra-high water-containing phase (Fan & Ma, 2011;Ma et al, 2015;Lin, Shan, & Chen, 2017b;Yang et al, 2017). Therefore, hunting for remaining oil, enhancing oil and gas output to attain the full potential are urgent problems to be solved.…”
Section: Introductionmentioning
confidence: 99%